2017
DOI: 10.5513/jcea01/18.1.1888
|View full text |Cite
|
Sign up to set email alerts
|

Impact of state aid on business decisions and financial stability of family farms in Croatia

Abstract: The aim of this paper is to identify farmers' attitudes towards the impact of state aid on business decisions and financial stability of farms. It will also identify the share of agricultural support in the total income of farms and the reasons for certain agricultural branches having unequal economic dependence on the support. Furthermore, it will investigate which of the two pillars of the CAP farmers consider being more important for their business and which factors would mostly contribute to the increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Ranogajec et al (2009) wrote about agriculture as a low-productive activity in Croatia, with small possibilities of accession to the relatively expensive loans, because the government is trying to foster agriculture by obtaining some more favourable funds for investment in agriculture: lower interest rates, longer repayment periods, contracting the grace periods, etc. Jež-Rogelj et al (2017) found that for most of the surveyed farms, subsides make up to 30% of income. Radović (2011) wrote about the model of transition of Slovenian agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Ranogajec et al (2009) wrote about agriculture as a low-productive activity in Croatia, with small possibilities of accession to the relatively expensive loans, because the government is trying to foster agriculture by obtaining some more favourable funds for investment in agriculture: lower interest rates, longer repayment periods, contracting the grace periods, etc. Jež-Rogelj et al (2017) found that for most of the surveyed farms, subsides make up to 30% of income. Radović (2011) wrote about the model of transition of Slovenian agriculture.…”
Section: Introductionmentioning
confidence: 99%